Experimental investigations on the potential of SDS as low‐dosage promoter for carbon dioxide hydrate formation. Issue 6 (25th March 2013) - Partoon, Behzad; Malik, Siti Nurmala A.; Azemi, M. Hazim; Sabil, Khalik M.
ABSTRACT A laboratory‐scale batch reactor is built and operated to study the kinetic of formation of carbon dioxide hydrate in deionized water and sodium dodecyl sulfate (SDS) solutions. In this experimental work, the formation of carbon dioxide hydrate in deionized water (18 Ω) is investigated at fixed temperature of 273.65 K and different pressures of 20, 25, 30, and 35 bar, respectively. The formation of carbon dioxide hydrate in SDS solutions is investigated by using various concentrations of SDS up to 3000 ppm at temperature of 273.65 K and 35 bar. For carbon dioxide hydrate, the induction time decreases with the increase of initial carbon dioxide pressure because of the increase of subcooling and driving force in the system. Moreover, experimental results show that the addition of SDS reduces the induction time required for hydrate formation and significantly increases the carbon dioxide uptake, and these effects are concentration dependent. Furthermore, the addition of SDS in the hydrate‐forming systems has been shown to improve the apparent rate constant of the system. These results show that SDS shows a good promise to be used as low‐dosage hydrate promoter to improve the efficiency of gas hydrate‐based processes. © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.